Efficacy of Monitoring the Sensory Taste Characteristics in Pomegranate Juice with Electronic Tongue and Chemical Measurements. Issue 6 (26th November 2014) - Bett‐Garber, Karen L.; Watson, Michael A.; Lea, Jeanne M.; Bai, Jinhe; Baldwin, Elizabeth; Raithore, Smita
Abstract Taste is imperative in pomegranate juice and is influenced by many production and processing factors. Measuring sweetness, sourness, bitterness, astringency and toothetch without a sensory panel makes economic sense. This investigation compares descriptive sensory evaluation (DSE) with physical methods. Brix degree (Brix), titratable acidity (TA), pH, methyl cellulose precipitable tannin assay (MCPTA) and electronic tongue (e‐tongue) techniques were measured in six commercial juices. The MCPTA correlated with astringent (r = 0.57, Pr = 0.01) and bitter (r = 0.58, Pr = 0.01), while pH negatively correlated with sour (r = −0.53, Pr = 0.02). DSE and physical measurements sufficiently differentiated brands. DSE could differentiate between five of the six brands. TA, Brix, pH and MCPTA tests differentiated between all six juice brands. The e‐tongue resulted in large differences within four of the brand as well as between brands. Evaluation of these methods by diluting one juice brand facilitated distinguishing how the methods work on the same compounds at declining concentrations. Practical Applications This study compares pomegranate juice chemical measures (Brix, pH, TA, MCPTA) with actual sensory taste and mouth feeling characteristics as well as introduces the e‐tongue as an application to monitor quality in processed pomegranate juice. The MCPTA assay reasonably correlated with astringency and can be utilized for estimating pomegranate juice astringency in place of sensory evaluation. The information reported is useful for testing juices in research settings and in monitoring juice production for quality assurance purposes.